(untitled) (Journal of Universal Science Research, 2024)
This article covers the expression of determiners and relative clauses in British English and its context opinion about the place, syntactic and semantic features and their types held. Determinants and their specific characteristics are analyzed. Analyzes tried to prove it based on several examples. A definite article the types of sentences and their participation in the sentence were observed. Linguist different controversial views of scientists about determiners in English have been studied, compared and summarized.